Determinants of Green Entrepreneurial Intention: A Systematic Literature Review Using the PRISMA Approach - Linda Oktavianti; Idris Idris; Efni Cerya (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This paper seeks to analyze factors, theoretical foundations, and research gaps in green entrepreneurial intention (GEI) through a Systematic Literature Review based on PRISMA. Data were drawn from 25 publication of scientific articles in Scopus-indexed journals during the 2020-2025 period and selected through the stages of identification, screening, eligibility assessment, and inclusion. Analytical results from this research reveal that GEI is influenced by individual factors, such as attitudes, perceived behavioral control, self-efficacy, and environmental awareness. Additionally, entrepreneurship education and institutional support also contribute to strengthening green entrepreneurial intent. The Theory of Planned Behavior stands as the most prominently utilized framework in GEI research. However, some studies have combined it with other theories such as the Resource Based View, Social Cognitive Theory, and Value Belief Norm to enhance the model’s ability to explain the phenomenon. This review also identifies research gaps, including the dominance of TPB usage, limitations in contextual and cultural studies, and the scarcity of research linking green entrepreneurial intentions to actual behavior. Therefore, this study contributes through a comprehensive literature synthesis and offers a future research agenda involving the development of an integrative theoretical model and more diverse methodological approaches to support sustainable entrepreneurship.